Tomato Pinworm, Keiferia lycopersicella (Walshingham) - Sidney L. Poe (EDIS, 2003)
The tomato pinworm is a small, microlepidopteran moth that is often confused with closely related species which have similar habits. This document is EENY-074 (originally published as DPI Entomology Circular No. 131), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 1999.